The Relationship Between Levels of Anxiety and Family Support with the Selection of Birth Attendants - Nurhikmah, Nurhikmah; Arsyad, Nur Aliya; Muliyana, Muliyana; Azis, Reskiawati (Poltekita : Jurnal Ilmu Kesehatan, 2023)
One of the psychological problems experienced by many pregnant women is their anxiety about choosing a birth attendant. This study aimed to analyze the influence of anxiety levels and family support on the selection of birth attendants. This study used a quantitative observational design and a cross-sectional approach. This study was carried out from November to December 2021 at the Bontomarannu Community Health Center, Gowa Regency, with a sample size of 32 pregnant women. Purposive sampling was used. The results of the study using the chi-square test showed that the level of anxiety was p = 0.007 and family support was p = 0.003 <a = 0.05. twelve pregnant women received poor family support, four (33.3%) respondents were good, and eight (66.7%) pregnant women were not good at choosing birth attendants, of the 32 respondents, 22 were pregnant women with mild levels of anxiety, 15 (68.2%) were good at choosing birth attendants, and 7 (31.8%) were not good. This means that there is a relationship between the level of anxiety and family support, and the choice of birth attendant. It is hoped that pregnant women who are anxious about choosing a birth attendant will always receive more assistance, whether from the family or a midwife so that there is no prolonged anxiety. Midwives are advised that in carrying out any midwifery care, they can identify problems and take action quickly and precisely, especially in carrying out ANC examinations for patients who are preparing for childbirth